1989
DOI: 10.1128/iai.57.3.673-678.1989
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and electron microscopic study of interaction of Yersinia enterocolitica serotype O8 with intestinal mucosa during experimental enteritis

Abstract: The experimental infection of mice with Yersinia enterocolitica serotype 08 was investigated in a quantitative and histological study. The course of bacterial penetration and spreading was precisely determined by immunohistochemical staining. After oral administration, the bacteria passed the epithelial barrier of the ileum and spread into the lamina propria. By preference they entered Peyer's patches, which were about 1,000 times more heavily colonized than the surrounding epithelium of a comparable surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(73 citation statements)
references
References 17 publications
3
70
0
Order By: Relevance
“…Taken together, our experimental data and the background of information discussed here suggest that the virulence plasmid of Y. enterocolitica codes for mechanisms that are required for the infection by the oral route. The presence of antibodies to plasmid-mediated OMPs in sera from patients recovering from infection with Y. enterocolitica [30] reveals that these proteins were expressed during the infection, but this does not necessarily mean a role other than that required for infection of intestinal tissues and spread into the lamina propia of the villi, as described by Hanski et al [27]. Differences between median lethal doses of isogenic pairs from serotypes other than 08 given i.p.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Taken together, our experimental data and the background of information discussed here suggest that the virulence plasmid of Y. enterocolitica codes for mechanisms that are required for the infection by the oral route. The presence of antibodies to plasmid-mediated OMPs in sera from patients recovering from infection with Y. enterocolitica [30] reveals that these proteins were expressed during the infection, but this does not necessarily mean a role other than that required for infection of intestinal tissues and spread into the lamina propia of the villi, as described by Hanski et al [27]. Differences between median lethal doses of isogenic pairs from serotypes other than 08 given i.p.…”
Section: Discussionmentioning
confidence: 94%
“…We have performed phagocytosis assays without antibiotic addition, and the microscope observations corroborated that IP383 was associated to macrophages but were not internalized, whereas IP383p-were internalized into phagosomes, although no differences were observed in bacterial counts of both strains after 4 h of incubation of the infected monolayer (data not included in the present work). The situation may differ in relation to PMN, which surrounded yersiniae-colonized area in the lamina propia after infection by the oral route [27]. Recently, China et al [28] described that the presence or the absence of YadA in the surface of Y. enterocolitica correlates respectively with resistance or susceptibility to phagocytosis and killing by human PMN.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, upon restriction of the expression of b1 integrins to the basolateral surface during differentiation of enterocytes, yersiniae are no longer able to invade these cells from the apical side (Coconnier et al, 1994;McCormick et al, 1997;. These studies have been confirmed by electron microscopic in vivo studies (Hanski et al, 1989;Autenrieth and Firsching, 1996).…”
Section: Introductionmentioning
confidence: 87%
“…Yersina spp. establish infection by well-orchestrated steps, beginning with bacterial secretion followed by polarized translocation of effector proteins, Yops ( Yersinia outer proteins) into a target host cell to prevent bacterial uptake, a process termed anti-phagocytosis (Hanski et al, 1989;Simonet et al, 1990;Forsberg et al, 1994). The virulence plasmid encodes about 11 independent Yops, each responsible for individual functions ranging from circumventing an intrinsic host cell response to regulatory functions.…”
Section: Introductionmentioning
confidence: 99%